Modelling and Seismic Response Analysis of Non-residential Single-storey Existing Precast Buildings in Italy. Issue 4 (12th March 2023) - Bosio, Marco; Di Salvatore, Chiara; Bellotti, Davide; Capacci, Luca; Belleri, Andrea; Piccolo, Valeria; Cavalieri, Francesco; Lago, Bruno Dal; Riva, Paolo; Magliulo, Gennaro; Nascimbene, Roberto; Biondini, Fabio
ABSTRACT: Old precast buildings are often characterized by poor detailing that may hamper the structural performance, particularly in the case of earthquakes. This is essentially related to: (i) a limited past knowledge of seismic design and behaviour, also reflected in past building codes; (ii) the evolution of seismic zonation of the Italian territory. The aim of this work is to assess the probabilistic seismic vulnerability with respect to the usability preventing damage and global collapse performance levels of four existing single-story precast buildings designed in accordance with past Italian building codes from 1960s to 1990s in three sites with increasing seismic hazard.